EFFECT OF MANAGEMENT EFFICIENCY ON FINANCIAL PERFORMANCE OF SAVINGS AND CREDIT SOCIETIES IN KENYA - Barus, Jane J.; Muturi, Prof. Willy; Kibati, Dr. Patrick; Koima, Dr Joel (Journal of Strategic Management, 2017)
Purpose: The purpose of this study was to evaluate the effect of management efficiency on financial performance of savings and credit societies in Kenya. Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO's in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was used in the study. Both primary and secondary sources of data were employed. Multiple linear regression models were used to analyze the data using statistical package for the social sciences (SPSS) and STATA. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive and inferential analysis was conducted to analyze the data. The data was presented using tables and graphs. Results: Based on the findings the study concluded that management efficiency has no significant influence on the financial performance of savings and credit societies in Kenya. The univariate regression results showed that management efficiency has no significant influence on the financial performance of savings and credit societies (p=0.173). Unique contribution to theory, practice and policy: The study recommended that with regard to credit risk management, the management should undertake measures to improve Capital adequacy, Asset quality, Management efficiency, Earnings and Liquidity. Further, the study recommended that SACCO's should train their employees as this is likely to increase their productivity.